The possible association between Chlamydia pneumoniae infection and asthma. - Al-Zaidi, Mahmood Sh.; Kadhim, Haider S.; Ahmed Shemran, Haider (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Many etiological factors have been implicated in the pathogenesis of Asthma like; viruses, bacteria and Chlamydia pneumoniae. This study focuses on the role of Chlamydiapneumoniae in asthma pathogenesis.Patients and Methods: The detection of Anti-Chlamydia pneumoniae antibodies IgA, IgM and IgG in patients by ELISA, for 35 patients, 18 asthmatic patients, 12 patients with chest infection with no history of asthma, and 5 apparently healthy as control subjects.Results: The results showed that 80% and 70% of the patients were negative for anti- Chlamydia pneumonia antibodies IgA and IgM respectively, while significantly (p